Forest Types of Pashupati Sacred Grove, Kathmandu, Nepal - Shrestha, Laxmi J; Devkota, Mohan (Journal of Natural History Museum, 2015)
A year round phytosociological study was carried out in 2012 to study different forest types in Pashupati Sacred Grove in Kathmandu Valley. Concentric circular plots (n-19) were laid down along eight parallel transects, 100 m apart from each other, traversing north and south passing through various vegetations. Our results showed that the grove had experienced change in forest types over the time period. Three forest types namely Schima-Pyrus, Moist (Myrsine- Persea) and Mixed (Quercus-Myrsine) were identified based on the importance value Index (IVI) of tree species instead of Myrsine-Schima forest which had once dominated the grove. Tree density greatly changed in different forest types and showed strong correlation between canopy cover and tree density, supporting the results of previous studies. J. Nat. Hist. Mus. Vol. 27, 2013: 72-77